Disponibilidade de fósforo do solo, crescimento, nutrição e micorrizas em mirtáceas nativas - Mattei, Greice (2013)
Knowledge of nutritional requirements and ecological relationships of native tree species is of great importance in forest restoration projects. The effects of soil phosphorus (P) availability on growth of native Myrtaceae of southern Brazil and the interaction of this factors on nutrient concentration of leaves and the occurrence of arbuscular mycorrhizal fungi (AMF), and the prevailing mycorrhizal structures were evaluated. A field experiment was carried out in Mato Castelhano, Rio Grande do Sul state, Brasil, from september 2010 to april 2012, by using plants with eight months after germination. A completely randomized design with tree repetitions was used in a 6 x 3 factorial arrangement, involving six species (Eugenia uniflora, Eugenia pyriformis, Eugenia involucrata, Campomanesia xanthocarpa, Campomanesia guazumifolia and Myrcianthes pungens) and tree levels of soil P availability (low, high and very high). Soil acidity and other nutrients availability were corrected for all treatments. After twenty months of cultivation, the wet and dry matter of the shoot was evaluated. It was evaluated the height and stem diameter of plants, calculated the growth rate and analyzed the content and accumulation of macro and micronutrient on leaves. Mycorrhizal levels and prevailing mycorrhizal structures were evaluated. Growth variables, content and accumulation of macro and micronutrients were not influenced by the interaction between P levels and species, but varied with the latter factor. The P content of leaves was greatest with the increased of the soil availability of this nutrient. This factor and the plant specie influenced mycorrhizal colonization, which was highest at Eugenia uniflora, Eugenia pyriformis and Campomanesia guazumifolia. The prevailing mycorrhizal structures were hyphae and intraradical vesicles